STUDI IKATAN HIDROGEN PADA ORIENTASI MOLEKUL DISPERSE RED-1 DENGAN METODE PVD BERBANTUAN MEDAN LISTRIK - Johana P. Tampi; Donny Royke Wenas; Marianus (Jurnal FisTa : Fisika dan Terapannya, 2020)
Organic molecules with a conjugated chain structure such as the Disperse Red-1 (DR-1) molecule are known as potential materials for photonic device applications. The aim of this research is to study the surface effect of Indium Tin Oxide (ITO) substrate and the external electric field of 2.6 MV / m in regulating the orientation of the DR-1 film molecules on the surface of the ITO substrate. The fabrication method used is the PVD (Physical Vapor Deposition) method assisted by an external electric field. This method is a modification of the conventional PVD method which is equipped with the addition of an external electric field (E) in the chamber. The film was made on the surface of the ITO substrate with the deposition of DR-1 molecules in a variation of the external electric field, namely zero field and E = 3.3 MV / m. The films were analyzed and characterized using XRD (X-Ray Diffraction) spectroscopy. The X-ray diffraction measurement analysis showed that the DR-1 molecules were arranged in an orderly manner parallel to the surface of the ITO substrate, indicating an indication of the strong surface effect of the ITO substrate from the hydrogen bonding of the DR-1 molecule with the ITO substrate. The results of spectroscopic measurements show that with an increase in the external electric field, there is an increase in the effect of aggregation of molecules arranged in an orderly manner perpendicular to the surface of the ITO substrate.